1996
DOI: 10.3354/meps139095
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and life history traits of the benthopelagic mysid Boreomysis oparva from the eastern tropical Pacific oxygen minimum zone

Abstract: ABSTRACT-The ecology and life h~story traits of Boreomysis oparva, a recently described benthopelagic mysid, were examined from the seamount Volcano 7 which penetrates into the oxygen minimum zone. In the near-bottom waters, B. oparva was very abundant at the lower summ~t In the oxygen minimum zone (<0.2 m1 O2 I-'). It decreased in abundance with increasing depth and Increasing oxygen at the flank and was absent from the base of Volcano 7. Length distribution of free-living stages was continuous, from 4 to 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Little is known about the factors affecting brood size, although a study on R. hastatus by Yolanda et al (2023) indicated a substantial correlation between the size of the brood and the length of the brooding females. This indicates that a larger marsupial mother is capable of producing and caring for a larger brood ( Saltzman, 1996 ). Figure 4 shows the general life cycle of mysids that have been modified from McKenney (2005) .…”
Section: Survey Methodologymentioning
confidence: 99%
“…Little is known about the factors affecting brood size, although a study on R. hastatus by Yolanda et al (2023) indicated a substantial correlation between the size of the brood and the length of the brooding females. This indicates that a larger marsupial mother is capable of producing and caring for a larger brood ( Saltzman, 1996 ). Figure 4 shows the general life cycle of mysids that have been modified from McKenney (2005) .…”
Section: Survey Methodologymentioning
confidence: 99%
“…Occurrences of a large overwintering generation and a small summer generation found in O. japonica agree with the general traits of mysid species in mid-latitude regions (Mauchline 1980). Within mysid species, larger individuals generally produce more, and larger, eggs (Saltzman 1996). Therefore, because females are larger at lower temperatures, brood size and egg size also tend to be larger at lower temperatures (Murano 1964, Toda et al 1982, Yamada & Yama shita 2000.…”
Section: Seasonal Changes In Population Structurementioning
confidence: 99%
“…Fecundation occurs externally in the marsupium, the structure where females carry their embryos during the entire larval development (Tattersall & Tattersall 1951;. The number of embryos in the marsupium varies inter-and intraspecifically according to female size Biju & Panampunnayil 2010;, embryo size (Saltzman 1996;Hanamura et al 2008), and seasonally, with larger brood sizes usually occurring during warmer months . Embryos per female generally range from <5 to 245, this figure being usually higher for coastal and epipelagic species than for oceanic ones .…”
Section: Chapter 1 Introductionmentioning
confidence: 99%